Mental fatigue and technical performance in elite rugby league - Mariano, Y.; Martin, K.; Mara, J. (Journal of Sports Sciences, 2023)
The aims of this study were to determine the impact of elite rugby league competition on mental fatigue; and to investigate how mental fatigue influenced in-match technical performance. Twenty elite male rugby league players recorded their pre- and post-game subjective mental fatigue and had their technical performance analysed during matches across one competition season. Metrics were created to assess in-match technical performance and described the percentage of positive, neutral, and negative involvements for each player, while accounting for the context and difficulty of each involvement. Self-reported mental fatigue increased from pre-game to post-game (maximum a posteriori estimation [MAP] = 33.1, 95% high-density interval [HDI] = 26.9-39.8), with backs reporting higher changes in mental fatigue than forwards (MAP = 18.0, 95% HDI = 9.7-26.9). Larger increases in mental fatigue from pre-game to post-game were negatively associated with the adjusted percentage of positive involvements metric (MAP = -2.1, 95% HDI = -5.6 to 1.1). Elite rugby league players reported increased mental fatigue following competitive games, with backs reporting a greater increase than forwards. Mental fatigue impacted technical performance, whereby participants had a lower percentage of positive involvements when they reported being more mentally fatigued.